2003
DOI: 10.1046/j.1365-2265.2003.01725.x
|View full text |Cite
|
Sign up to set email alerts
|

The outcome in Australian children with hyperinsulinism of infancy: early extensive surgery in severe cases lowers risk of diabetes

Abstract: Poor neurodevelopmental outcome remains a major problem in hyperinsulinism of infancy. Risk of diabetes mellitus with pancreatectomy varies according to age at surgery and extent of resection. Patients presenting early with severe disease have a better neurodevelopmental outcome and lower risk of diabetes if they are treated with early extensive surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
38
2
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 32 publications
5
38
2
1
Order By: Relevance
“…Indeed, de Lonlay-Debeney et al 10 reported normoglycemia among 21 neonates with focal hyperinsulinism who underwent partial pancreatectomy, whereas 15 of the 30 neonates with diffuse hyperinsulinism who underwent total pancreatectomy developed hyperglycemia and 19 of 30 developed exocrine pancreatic insufficiency in the subsequent 4 years. Similarly, large follow-up studies of patients with PHHI noted diabetes mellitus in Ͼ25% of cases with near-total pancreatectomy 14,19,20 and exocrine pancreatic insufficiency in 20% of cases. 2,14 Laparoscopic enucleation of a focal lesion has not been reported previously, whereas laparoscopic subtotal pancreatectomy for treatment of PHHI was reported once.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Indeed, de Lonlay-Debeney et al 10 reported normoglycemia among 21 neonates with focal hyperinsulinism who underwent partial pancreatectomy, whereas 15 of the 30 neonates with diffuse hyperinsulinism who underwent total pancreatectomy developed hyperglycemia and 19 of 30 developed exocrine pancreatic insufficiency in the subsequent 4 years. Similarly, large follow-up studies of patients with PHHI noted diabetes mellitus in Ͼ25% of cases with near-total pancreatectomy 14,19,20 and exocrine pancreatic insufficiency in 20% of cases. 2,14 Laparoscopic enucleation of a focal lesion has not been reported previously, whereas laparoscopic subtotal pancreatectomy for treatment of PHHI was reported once.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the aforementioned increased incidences of diabetes mellitus and exocrine pancreatic insufficiency related to subtotal pancreatectomy, up to 50% of patients with PHHI experience psychomotor or mental retardation. 19,20,22 Reasons include poor or delayed diagnosis of the condition or delayed surgery. 20 Early surgery (Ͻ100 days of age) is generally associated with improved neurodevelopmental outcomes and fewer endocrine and exocrine disturbances.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The combination of hypoglycaemia and lack of ketones places infants at high risk of neurological damage [128]. Thus rapid diagnosis and appropriate management are critical to prevent poor neurodevelopmental outcomes [129].…”
Section: Clinical Featuresmentioning
confidence: 99%